CRIMEAN-CONGO HEMORRHAGIC FEVER (CCHF); A CASE REPORT - Zareen, Syeda Fatimah; Abbas, Syed Waqar; Khurshied, Saleh; Bukhari, Syed Karamat Hussain (Pakistan Armed Forces Medical Journal, 2020)
Crimean Congo Hemorrhagic Fever (CCHF) one of the fatal viral infections has been described in around 30 countries around the world and is endemic in some parts of Pakistan. The fever is transmitted to humans by the bite of an infected tick either by direct contact with the blood or tissue via infected humans and livestock. We present here case of a 34-year-old Pak defense services officer who reported with nonspecific symptoms of high grade fever, myalgias and vomiting but rapidly deteriorated and developed bleeding diathesis. He was diagnosed to have CCHF and managed with Ribavirin, repeated transfusions and IV fluids with strict nursing barrier and use of Personal Protective Equipment (PPE). The patient recovered well.